2015
DOI: 10.1111/gcbb.12291
|View full text |Cite
|
Sign up to set email alerts
|

Candidate perennial bioenergy grasses have a higher albedo than annual row crops

Abstract: The production of perennial cellulosic feedstocks for bioenergy presents the potential to diversify regional economies and the national energy supply, while also serving as climate 'regulators' due to a number of biogeochemical and biogeophysical differences relative to row crops. Numerous observational and model-based approaches have investigated biogeochemical trade-offs, such as increased carbon sequestration and increased water use, associated with growing cellulosic feedstocks. A less understood aspect is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
37
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(42 citation statements)
references
References 60 publications
5
37
0
Order By: Relevance
“…Evaporative cooling of miscanthus and switchgrass, therefore, is augmented by higher albedo, consistent with previous results (Anderson‐Teixeira et al ., ). However, observed experiment data indicated that miscanthus and switchgrass have a higher albedo than corn during the growing season, thereby reducing Rn in bioenergy crops (Miller et al ., ). This discrepancy likely originates from the current model being unable to predict albedo of these perennial grasses through improper parameterization of leaf transmittance and reflectance, leaf angle, and canopy structure (Lawrence et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…Evaporative cooling of miscanthus and switchgrass, therefore, is augmented by higher albedo, consistent with previous results (Anderson‐Teixeira et al ., ). However, observed experiment data indicated that miscanthus and switchgrass have a higher albedo than corn during the growing season, thereby reducing Rn in bioenergy crops (Miller et al ., ). This discrepancy likely originates from the current model being unable to predict albedo of these perennial grasses through improper parameterization of leaf transmittance and reflectance, leaf angle, and canopy structure (Lawrence et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…Albedo values were modified based on field site observation values obtained from Miller et al (2016). Seasonal profiles of albedo were determined by averaging daily albedo values across two perennial plant types (switchgrass and miscanthus) and across the observed years of 2010 and 2011.…”
Section: Perennial Bioenergy Crop Representation and Deployment Scmentioning
confidence: 99%
“…In addition, the importance of field-scale studies has demonstrated the significance of appropriate biogeophysical representation in process-based models that can be used to examine scenario-based environmental implications. For example, Miller et al (2016), via a multiyear observational campaign, conducted field-scale measurements to determine that perennial bioenergy crops have consistently higher values of albedo than annual crops during the growing season. This higher albedo can reduce the amount of solar energy received at the surface, affecting the partitioning of sensible, latent, and ground heat fluxes (Georgescu et al 2011(Georgescu et al , 2013Anderson-Teixeira et al 2012;Anderson et al 2013;Bagley et al 2015;Miller et al 2016).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The advantages of farmlands involving perennial crops and grasslands vs. annual crops is a topic of broad discussion and research over the past decade (e.g., Ferchaud et al, 2016;Miller et al, 2016;Vico et al, 2016). Several articles in this Research Topic focus on how different types of farmlands and other land uses are providing multiple long-term ecosystem services.…”
Section: Grasslands Perennial and High Nature-value Farmlandsmentioning
confidence: 99%